The Analytical Approach of Scientific Knowledge at Gaston Bachelard (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research highlights on an important and fundamental issue of the 20th century's most important philosophers, "Gaston Bachelard", which is the analytical approach to scientific knowledge of this philosopher and the role played by "Gaston Bachelard" in this approach in formulating a set of scientific concepts that enriched epistemology as the concept of the epistemological obstacle ,The concept of  estrangement and the concept of undo time, with concentration on importance of the dialectical relationship between these concepts and their role in the development of scientific knowledge.